2021
DOI: 10.3390/bioengineering8090128
|View full text |Cite
|
Sign up to set email alerts
|

The “Federica” Hand

Abstract: Hand prostheses partially restore hand appearance and functionalities. In particular, 3D printers have provided great opportunities by simplifying the manufacturing process and reducing costs. The “Federica” hand is 3D-printed and equipped with a single servomotor, which synergically actuates its five fingers by inextensible tendons; no springs are used for hand opening. A differential mechanical system simultaneously distributes the motor force on each finger in predefined portions. The proportional control o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…In addition, the current uniform distribution of the actuator torque among the four exoskeleton fingers may evolve into a differential distribution [26], to better exploit the redundancy of the fingers in grasping objects of different shapes and textures and provide a more effective adaptive grip. However, some current limitations should be addressed in future studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the current uniform distribution of the actuator torque among the four exoskeleton fingers may evolve into a differential distribution [26], to better exploit the redundancy of the fingers in grasping objects of different shapes and textures and provide a more effective adaptive grip. However, some current limitations should be addressed in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed the high similarity between the EMG-LE and the signal obtainable from a custom force sensor capable of detecting the mechanical activity of muscles (referred to as force-myography (FMG)) [24]. The advantages deriving from the use of FMG instead of EMG are various [25]: the problems related to EMG recording and its processing are avoided; the force sensor output can be used as is (no processing is required) and has already been successfully demonstrated for various applications (hand prosthesis control [26][27][28][29]; hand gesture recognition [30,31]; physiological parameters monitoring [32][33][34]); moreover, a very recent study suggests that force sensors seem to perform better than EMG in daily activities for exoskeleton controls [35].…”
Section: Introductionmentioning
confidence: 99%
“…Forcecardiography is a novel technique based on specific wearable force sensors that measure the local forces induced on the chest wall by the mechanical activity of the heart and lungs [ 110 , 111 , 112 , 113 , 114 , 115 ]. FCG signals were first acquired by means of sensors based on force-sensing resistors (FSR), which have already proved suitable for muscle contraction monitoring [ 116 ], gesture recognition [ 117 ], and the control of biosignal-based human–machine interfaces [ 118 ], such as the “Federica Hand” prosthesis [ 119 , 120 , 121 , 122 ] and an upper-limb exoskeleton [ 123 ]. The use of such FSR-based sensors has also been demonstrated for continuous respiratory monitoring [ 114 ].…”
Section: Methodsmentioning
confidence: 99%
“…Esposito et al also presented an alternative approach to EMG, with comparable performances, for improved hand prosthesis control based on muscle contraction detection via an FSR-based sensor [143]. The sensor was placed on a forearm muscle, proving to be as effective as the EMG envelope to control a hand prosthesis prototype [155,156]. Ha et al explored the prediction of hand gestures by applying piezoelectric sensors around the forearm to map muscle contraction [157,158].…”
Section: Muscle Gross Motion-based Hmismentioning
confidence: 99%